Two‐Dimensional MXene Supported Bismuth for Efficient Electrocatalytic Nitrogen Reduction. Issue 7 (8th February 2022) - Liu, Anmin; Liang, Xingyou; Zhu, Haiding; Ren, Xuefeng; Gao, Liguo; Gao, Mengfan; Yang, Yanan; Li, Guangxin; Ma, Tingli
Abstract: Electrochemical nitrogen reduction reaction (NRR), as a green and sustainable ammonia (NH3 ) synthesis process, is considered to be the most promising alternative to the traditional Haber‐Bosch method for NH3 synthesis. However, this process requires a highly active electrocatalyst to overcome the problems of low NRR activity and selectivity. Herein, we deposited metallic bismuth nanoparticles on two‐dimensional Ti3 C2 MXene nanosheets by a simple liquid phase reduction method to synthesize Bi@Ti3 C2 nanocomposites. This composite material is a promising electrocatalyst for environmental electrocatalytic N2 fixation to NH3 . Unexpectedly, the Bi@Ti3 C2 composite obtains an excellent NH3 yield and Faraday efficiency as high as 28.3 μg h −1  cm −2 and 27.2 % at −0.4 V versus reversible hydrogen electrode (RHE) in 0.1 M KOH. The high NRR activity can be attributed to the unique N‐philic and H‐phobic characteristics of Bi atoms and the outstanding electronic conductivity of MXene. Moreover, the Bi@Ti3 C2 composite catalyst also exhibited good cycling stability and durability of up to 24 h. This work highlights the potential importance of material design and will also expand the research and exploration of high‐efficiency NRR electrocatalysts. Abstract : N and H : Synthesized in one step by the liquid‐phase reduction method, Bi@Ti3 C2 MXene nanocomposite catalyst achieved high NRR activity with excellent NH3 yield of 28.3 μg h −1  cm −2 and Faradaic Efficiency of 27.2 % at −0.4 V with good selectivity in 0.1 M KOH solution, profiting from the unique N‐philic and H‐phobic characteristics of Bi atoms and the outstanding electronic conductivity of MXene.